A thematic analysis of the challenges experienced by those living with tuberculosis - Walaza, Robert Letsholo (Rhodes University, Faculty of Humanities, Department of Sociology, 2018)
Friedrich Engels (1820-1895) in his study, The condition of the working class in England, argued that the cause of illness and death amongst the working class was due to their living conditions such as poor housing, over-crowding, poor sanitation, food shortage, low paying jobs and a lack of material resources. The objective of the study was to understand the experiences of six South African individuals who have shared their experiences and challenges of living with TB on the TB&ME blog, and to show how TB is linked to the living conditions of these individuals. The study found that the challenges experienced by TB patient bloggers are of a social nature and confirms Engel's study findings on the conditions of the working class in England. For example, a disease such as TB has a direct association with the living conditions of people, especially the poor. Thus, socio economic status of TB patient bloggers plays a role in the escalation of their ill health. Further, the study found that gender is central in understanding non-compliance to treatment. This is significant as it highlights the need to not only focus on issues of socioeconomics, but gender issues in fighting TB. Despite the negative consequences associated with living with TB, the bloggers have noted that the support from loved ones and other stakeholders in the fight against TB alleviates the challenges inherent in living with TB.
Keywords: Tuberculosis Patients -- South Africa; Tuberculosis -- Social aspects; South Africa -- Social conditions; Poor Health and hygiene -- South Africa; Poor Medical care -- South Africa; Social medicine -- South Africa